Study of obstetric and perinatal outcome of twin pregnancy - Mehta, Chandni V.; Patel, Babulal S.; Shah, Akshay C.; Jani, Shashwat K.; Shah, Dipal C.; Patel, Vismay B.; Patel, Adwait B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Multifetal pregnancy constitutes a significant portion of high-risk pregnancies. This is due to the increasing obstetric and perinatal morbidity and mortality rates associated with it. Maternal and perinatal outcome of twin pregnancies has been evaluated in this study. Methods: Total 30 patients with twin pregnancy and having gestational age more than 28 weeks were included in this observational study. Results: Incidence of twins in the study was found to be 2%. Twin pregnancies were more common in multiparous women aged between 20 and 30 years. Most common foetal presentation was vertex- vertex presentation. Most common maternal complication was preterm labour seen in 67% women, followed by anaemia seen in 50% women. Most of the women were delivered by caesarean section (63.3%). Most common perinatal complication was birth hypoxia (41.6%). Other perinatal complications were jaundice, septicemia, intrauterine growth restriction. 71% of the neonates had birth weight less than 2.5 kg. Perinatal mortality was found to be 11.6%. Conclusions: Twin pregnancies are high risk pregnancies associated with higher obstetric and perinatal morbidity. Perinatal morbidity was more common for the second coming twin. Regular antenatal visits, planned delivery and better NICU facilities can help combat these complications. A team of skilled obstetricians and pediatricians along with a multidisciplinary approach is essential for the effective management of twin pregnancies.